The Annole Monument and Negus Menelik’s Expedition towards Arsi: A Bibliographic Essay - Tariku, Ayele (Ethiopian Journal of Social Sciences, 2018)
The formation of state in every society passes through different stages and mechanisms. In most cases, state formation involves one of these three forms: peaceful, forceful or a mixture of both. The current Ethiopian state is the result of all three forms. In the second half of the 19th century, Emperor Tewodros II (r.1855-1868) appeared in the political scene with a stronger vision to rule Ethiopia with one central administrative system, and culminated in the Era of Princes. The centralization project continued during the reign of Emperor Yohannes IV (r.1872-1889). In the last quarter of the same century, when the unification motto was common in Italy and Germany, Emperor Menelik II (1889-1913) strengthened the project and amalgamated different regions of northern and southern Ethiopia into his empire including Arsi. Many of the regions in southern Ethiopia were incorporated into his empire through forceful as well as peaceful measures between the years 1870 and 1900. These measures formed the current territorial shape of Ethiopia. There are two major different views concerning the process of state formation of the modern Ethiopian empire. These are the reunification and the colonial views. The colonial view maintains that until its incorporation, Oromia was an independent state and it was historically and culturally different from the northern part of Ethiopia. Thus, the expedition was colonial in its motive, nature and consequences. The reunification thesis on the other hand, advocates that the Oromo and all the people in the south had for ages been part and parcel of Ethiopia and lived together. Accordingly, the expedition did not have any colonial motive or nature. It aimed at reincorporation and protecting the people from external threat, extraction of natural resources and bring peace and stability. The paper examines how scholars addressed this issue in their publications in the 1980s and 1990s (G.C.). This paper does not attempt to endorse or reject any of these views. Instead, this essay aims to critically examine how scholars discursively understand and reflect the same issue differently.